Sustainable MSME Development and Inclusive Economic Growth: Evidence from Thailand - Nattapong Siriphan; Sornchai Kerdsuk (IJED: International Journal of Economy Development Research, 2026)
This study examines the role of sustainable micro, small, and medium enterprise (MSME) development in promoting inclusive economic growth in Thailand. MSMEs are vital to Thailand’s economy because they generate employment, support local livelihoods, strengthen rural economies, and contribute to national competitiveness. However, MSMEs also face challenges related to digital transformation, access to finance, environmental sustainability, market competition, and post-pandemic recovery. Using a qualitative-descriptive approach based on literature review and policy analysis, this study explores how sustainable MSME development contributes to inclusive economic growth. The findings show that sustainable MSMEs can support employment creation, poverty reduction, women’s economic participation, digital entrepreneurship, local innovation, and environmentally responsible production. However, the effectiveness of MSME development depends on stronger policy coordination, access to green finance, digital literacy, market access, and capacity-building programs. This study concludes that MSMEs in Thailand can become a strategic driver of inclusive and sustainable growth when supported by innovation, sustainability-oriented policies, and inclusive financial ecosystems